A social identity analysis of dissident Irish republicanism in Northern Ireland - de Heus, Annabelle L. (2019)
Although Northern Ireland has become a more peaceful place since the Good Friday Agreement, spoiler groups in the form of dissident republicans remain persistent in their opposition. This thesis analyses the role of social identity as a vehicle for understanding dissident Irish republicanism in Northern Ireland. Social Identity is a theory for understanding social psychological phenomena relating to group structures and intergroup relations. By focussing on dissident republicanism, and its relation to the Republican mainstream as characterised by Sinn Féin, this thesis finds that the political and personal identity of dissident groups and their members is best understood as a reaction to the out-group. This study argues that the relative strength of the mainstream out-group in the wider republican communities has a positive impact in terms of supressing dissident republican violence, but arguably also a negative impact in terms of countering legitimate political opposition.